Quality of the Teaching Process and its Factors of Influence from the Perspective of Future Business Specialists - Alexandra-Maria Drule; Irimie Emil Popa; Razvan Nistor; Alexandru Chis (Amfiteatru Economic Journal, 2014)
In the context of the large number of Romanian economic graduates competing for a relatively small number of specialized positions, an increasingly dynamic environment that requires specialists and leaders with practical skills, internationalization and increasing competition among higher education institutions to attract both students and financing, it is necessary to evaluate the quality and performance of business educational programs. Periodic evaluation is the premise of improving and modernizing educational services, and students, as the primary beneficiaries of education, are the first to be included in this process. Therefore, the goal of this research is to identify the perceptions of students specializing in the financial management of European funds regarding the quality of teaching staff and the teaching process. This study takes a quantitative approach using a survey method and a questionnaire as a data collection instrument. The questionnaire includes a set of 11 specific items that are considered to be most relevant to the quality of higher education services and two related to overall perceptions of quality. Data were collected from a sample of more than 1,500 students enrolled in a new master's program on the axis specified above. Analyses showed that three factors have a significant influence not only on the assessment of teacher performance during courses and seminars but also on the quality of the teacher involved in the process: the use of modern teaching techniques, the degree to which master's students are trained and actively participate in teaching activities, and the presentation of quality and coherent information. A teacher's performance is influenced to a lesser extent, but still a significant one, by other two items included in this study: delivering materials on time and efficiently using the time allocated to the discipline. However, professor performance is also negatively correlated with the relevance of the information offered to students and the difficulty of the assessment. This study offers a valuable perspective on the quality of the educational process as perceived by Romanian university students. It identifies the most relevant factors in ensuring the quality of a master's program focused on providing practical skills and training international specialists in the area of international funds management.
Keywords: A20; M30; M31; 330; quality of services; students; business educational programs; factors; perceptions; Romania